2016
DOI: 10.5350/bmb2016010101
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of cardiac myxomas in elderly patients

Abstract: Objective: Cardiac myxoma usually presents during early adulthood. There is generally a tendency for prompt surgical resection. However, advanced age of patients presenting with this disease may increase the operative risk due to other cardiac and non-cardiac problems. Therefore, we evaluated elderly patients who underwent surgery for myxoma to review the management of treatment. Methods:Between September 1985 and March 2012, a total of 17 consecutive patients over 65 years of age (5 male, 12 female; mean age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…With increasing life expectancy, however, the incidence of myxomas is rising in the elderly, creating challenges for surgical treatment [ 8 , 15 ]. A recent study reported about 25% mortality in the geriatric population undergoing cardiac surgery with a mean age of ~69±4 years at the time of surgery [ 16 ]. There have been reports of no surgical intervention, but the literature is silent about non-surgical management, follow-up, and prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing life expectancy, however, the incidence of myxomas is rising in the elderly, creating challenges for surgical treatment [ 8 , 15 ]. A recent study reported about 25% mortality in the geriatric population undergoing cardiac surgery with a mean age of ~69±4 years at the time of surgery [ 16 ]. There have been reports of no surgical intervention, but the literature is silent about non-surgical management, follow-up, and prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 4 8 ] In elderly patients with comorbidities, surgery is associated with a significantly increased risk of death of up to 23.5%. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…24 With respect to geriatric patients, a recent study evaluated elective surgery in elderly patients with myxomas. 15 During the time frame, 1985-2012, 17 consecutive patients (mean age ~69 ± 4 years) were evaluated. Overall, 13 patients survived resection with a relatively high mortality rate of nearly 25%.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Our patient had atrial fibrillation, which was coincident in almost 30% of patients. 5 , 15 The emergence of heart failure is contingent on tumor location and burden in creating a pseudo-stenotic effect due to malapposition of mitral valve leaflets and obstructive physiology within the left ventricular outflow tract. 16 Also, it has been postulated that a paraneoplastic cytokine milieu may induce myocardial inflammation and resultant ischemia.…”
Section: Discussionmentioning
confidence: 99%